Spawning behavior of Arctic charr (Salvelinus alpinus) : Spawning synchrony, vibrational communication, and mate guarding - Brattli, Magnus B.; Egeland, Torvald Blikra; Nordeide, Jarle Tryti; Folstad, Ivar (Ecology and Evolution, 2018)
A mismatch in synchrony between male and female gamete release in external ferti - lizers can result in reduced or failed fertilization, sperm competition, and reduced paternity. In Arctic charr ( Salvelinus alpinus ), males can adopt either a guard or sneak tactic resulting in both pre- and postcopulatory competition between males with al - ternative reproduction tactics. Here, spawning behavior of free- living Arctic charr was video- recorded, and their reproductive behavior was analyzed. From evaluating 157 spawning events, we observed that females mainly spawned with a guarding male and that the female and the guarding male synchronized timing of gamete re - lease under sperm competition. Although sneakers spawned with higher synchrony than the guarding male in single- male spawning events, the average sneaker released his milt less synchronized with the female than the guarding male under sperm com - petition. Approximately 50% of the recorded spawning events occurred under sperm competition, where each event included an average of 2.7 males. Additionally, sneak - ers were more exposed to sperm competition than guarding males. An influx of males, in close proximity to the female, occurred during the behavioral sequences leading up to egg release, but this influx seemed not dependent on egg release, sug - gesting that something else than gonadal product attracts sneaker males to the spawning female. Just before and during the actual release of gametes, the spawning couple vibrates their bodies in close contact and it seems likely that this vibrational communication between the spawning couple, which results in a larger amplitude sound wave than seen under regular courting, reveals time of gamete release to sneaker males. Thus, vibrational communication may enable synchrony between the guarding male and the female, and this might be traded against the cost of higher detectability from surrounding sneaker males, eavesdropping in close proximity. publishedVersion